1995
DOI: 10.1136/gut.37.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection density and gastric inflammation in duodenal ulcer and non-ulcer subjects.

Abstract: The factors that determine which Helicobacter pylorn infected subjects develop duodenal ulcer (DU) are unclear. This study tested the hypothesis that infection density and urease activity are higher in DU than non-DU subjects. Fifty five DU and 55 age and sex matched non-DU subjects were studied. Quantitative methods were used for measuring infection density (viable organism count) and urease activity (Berthelot reaction). DU subjects had a greater antral infection density ( Studies have attempted to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 20 publications
13
76
0
4
Order By: Relevance
“…Consistent with the fact that H. pylori colonization is greater in the antrum versus the gastric body (140,141), the extent of expression of both iNOS and COX-2 has been seen to also be considerably higher in the antrum. However, it should be noted that a recent study showed inflammation levels that were not significantly higher in the antrum versus the gastric body, which suggests a direct effect of H. pylori on the induction of expression for both genes (116).…”
Section: Changes In the Expression Of Enzymes Related To Inflammationsupporting
confidence: 65%
“…Consistent with the fact that H. pylori colonization is greater in the antrum versus the gastric body (140,141), the extent of expression of both iNOS and COX-2 has been seen to also be considerably higher in the antrum. However, it should be noted that a recent study showed inflammation levels that were not significantly higher in the antrum versus the gastric body, which suggests a direct effect of H. pylori on the induction of expression for both genes (116).…”
Section: Changes In the Expression Of Enzymes Related To Inflammationsupporting
confidence: 65%
“…In our study, the presence of activity was even more frequent in the cases negative for bacteria (72.3%) than in H. pylori positive cases (53%), as observed in PHULL et al study (17) . Some authors have been reporting a association between the activity grade and the bacterial concentration (1,6,11,12,20) although some of them have reported that only this finding could have an association with the concentration of H. pylori (12,20) . Although in our study the incidence of activity was higher in biopsy specimens without the bacterium, their marked activity prevailed over the biopsy specimens that had a concentration of bacteria of 3+ (42%).…”
Section: Resultsmentioning
confidence: 99%
“…Since it was firstly described by Warren and Marshall in 1983, Helicobacter pylori (H. pylori) etiologic relevance has been emphasized (17,18) in many gastrointestinal tract and esophageal diseases as being reported to cause gastritis, peptic ulcers, dysplastic lesions, gastric adenocarcinoma, gastric lymphomas (7,8,12,14,17,19,22) and a possibly cause of non-ulcer dyspepsia (7) . In developing countries, the infection is acquired during childhood, compromising around 90% of the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerca de 27 casos positivos pelo método citológico foram negativos pela histologia: a escova de citologia abrange uma área maior a ser estudada e estes dados sugerem ser a citologia mais sensível que os métodos que se utilizam de biópsia na identificação do Helicobacter pylori. O microrganismo está distribuído irregularmente no muco gástrico na superfície epitelial, e a relativa baixa densidade da bactéria em vários grupos de pacientes pode levar a resultados falso-negativos em métodos de biópsia 12 . A comparação de um método que se utiliza do esfregaço obtido por um escovado gástrico -a citologia, com um método que se utiliza de biópsia -a histologia, influenciou na especificidade do primeiro que foi de 50,9%.…”
Section: Discussionunclassified